Culture and values - Lawrence S. Cunningham (Thomson/Wadsworth, 2006)
Trusted by professors of the humanities survey course for over twenty years, CULTURE AND VALUES covers Western cultures along with important non-Western cultures, providing students solid, accessible introductions to art, music, philosophy, literature, and more. Available in two volumes, or as an alternate single volume without end-of-chapter readings, this text remains the most readable and reliable textbook for college and university students in the integrated humanities